Modifying Modifications: The Future of Child Support is Electronic. (8th January 2013) - Larson, Ryan
<x xml:space="preserve">Abstract</x> Child support arrears are growing across the country. The recent economic recession has only exacerbated the problem. One way of combating arrears is to ensure that child support orders are based upon accurate financial information. Parents and the state can do more to make this happen. This Note proposes that states implement, through administrative regulation, electronic modification systems that review support orders annually. Specifically, electronic systems would utilize automated noncustodial parent income data. Proposed models currently exist in states throughout the country and are consistent with due process afforded by the U.S. Constitution. Key Points for the Family Court Community Reforms to the child support modification process are needed. Suggestions are provided for keeping child support orders accurate and fair. Solutions are offered to help alleviate growing child support arrears. The intersection of technology and law is discussed.